2011
DOI: 10.1386/pjss.10.1.23_1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing deputies’ and voters’ support for Europe: The case of Portugal

Abstract: In this article, we compared and tried to explain deputies ' and voters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…There were important ideological differences between the two governments in office during this period. On the one hand, PS ( Partido Socialista , Socialist Party) had been moving towards the centre as a vote maximisation strategy in the decade prior to the bail‐out (Costa Lobo & Magalhães ; Moury & Sousa ) . On the other hand, the PSD leader, Pedro Passos Coelho, had been elected on a ‘neoliberal’ platform, departing from his forerunners and rivals who were more protective of social policies (Lisi : 137–138; Freire & Santana‐Pereira ).…”
Section: The Portuguese Sovereign Debt Crisis As a Case Studymentioning
confidence: 99%
“…There were important ideological differences between the two governments in office during this period. On the one hand, PS ( Partido Socialista , Socialist Party) had been moving towards the centre as a vote maximisation strategy in the decade prior to the bail‐out (Costa Lobo & Magalhães ; Moury & Sousa ) . On the other hand, the PSD leader, Pedro Passos Coelho, had been elected on a ‘neoliberal’ platform, departing from his forerunners and rivals who were more protective of social policies (Lisi : 137–138; Freire & Santana‐Pereira ).…”
Section: The Portuguese Sovereign Debt Crisis As a Case Studymentioning
confidence: 99%
“…Two different kinds of analysis -one based on interviews with Portuguese MPs conducted at the beginning of the crisis in 2008 (Moury & De Sousa, 2011), and the other based on the study of party manifestos in the period from 1995 to 2005 (Costa Lobo & Magalhães, 2011) -indeed converge to show that the two major parties, the PS and PSD, have a very strong pro-European attitude. However, these studies also show a difference within both mainstream and opposition parties.…”
Section: Theoretical Argument and Hypothesesmentioning
confidence: 99%
“…However, these studies also show a difference within both mainstream and opposition parties. While the manifestos of the three radical left parties (Leftist Bloc BE, the Communist PCP and the Greens PEV), which have never been in government, present strong anti-European stances, Moury and De Sousa (2011) observed that a large majority of BE deputies believes that EU membership is a good thing (66 . 7 per cent), in contrast to the small minority (29 per cent) of the CDU (PCP-PEV) deputies who agree with this statement.…”
Section: Theoretical Argument and Hypothesesmentioning
confidence: 99%
“…Obviously, this third hypothesis is related to the former as parties that are permanently out of government tend to be more Eurosceptic (Sitter, 2001;Taggart, 1998), while Eurosceptic parties that want to become credible coalition partners frequently moderate their hostility to Europe (Conti & De Giorgi, 2011;Costa Lobo & Magalha ˜es, 2011). Two different kinds of analysis -one based on interviews with Portuguese MPs conducted at the beginning of the crisis in 2008 (Moury & De Sousa, 2011), and the other based on the study of party manifestos in the period from 1995 to 2005 (Costa Lobo & Magalha ˜es, 2011) -indeed converge to show that the two major parties, the PS and PSD, have a very strong pro-European attitude. However, these studies also show a difference within both mainstream and opposition parties.…”
Section: Theoretical Argument and Hypothesesmentioning
confidence: 99%